In vivo modification of retroviral gag gene-encoded polyproteins by myristic acid. - Schultz, A M (1983)
It has recently been shown by mass spectral analysis (Henderson et al., Proc. Natl. Acad. Sci. U.S.A. 80:339-343, 1983) that the p15gag protein of murine leukemia viruses contains a novel post-translational modification, an amino-terminal myristyl (tetradecanoyl) amide. In this report we show that p15gag is the only structural protein to contain this fatty acid. In addition, the gag precursor polyproteins of type B, C, and D retroviruses have been examined for the presence of myristic acid by metabolic labeling and immunoprecipitation studies. In a panel of mammalian type C retroviruses we found that the precursor polyprotein Pr65gag homologs, but not the glycosylated forms (gPr80gag homologs), were specifically labeled after a 5-min incubation of infected cells with [3H]myristic acid. The gag precursor polyprotein was also labeled in mouse mammary tumor virus and in Mason-Pfizer monkey virus, but Pr76gag of Rous sarcoma virus failed to incorporate [3H]myristate. Under similar conditions, [3H]palmitate was not found to be incorporated into any viral gag proteins. Thus, myristylation appears to be a common feature of mammalian type B, C, and D retroviruses but not of avian retroviruses.